THE INFLUENCE OF FINANCIAL PERFORMANCE ON THE FIRM VALUE OF MINING COMPANIES WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATING VARIABEL - Ginting, Rasinta Ria; Pakpahan, Rut Maylani; Hutagalung, Galumbang; Pratama, Ayang; Tarigan, Aremi Evanta; Helman, Helman (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2026)
This research aims to empirically prove the influence of financial performance on company value projected by ROA, whether CSR is able to moderate the relationship between financial performance and company value. The data collection for this research comes from publications published on the Indonesian Stock Exchange (BEI) Data.The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2021. The sample in this research is manufacturing companies according to the specified criteria. The data analysis techniques used in this research are SPSS simple linear regression and moderated regression to determine the dependent variable which is influenced by the independent variable and hypothesis testing using t-statistics to test partial regression coefficients. The results of this study show that financial performance has a positive and significant effect on company value. The high and low ratio of net profit to total assets has implications for the high and low value of the company, meaning the high and low The ratio of net profit to total assets has implications for total assets and has implications for the level of company value. Likewise, CSR is able to moderate financial performance on company value, meaning that CSR disclosure can strengthen the relationship between financial performance which has implications for increasing company value.